Carbon nanotube complex, semiconductor device obtained by using the same and method for manufacturing the same, circuit, radio communication device, thin film transistor array and sensor
By attaching a conjugated polymer to carbon nanotubes, the carbon nanotube composite achieves high n-type semiconductor properties, addressing the limitations of existing CNT-FETs in logic circuits and enhancing operating speed and information processing.
Patent Information
- Application Number
- JP2024118397
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-06
- Filing Date
- 2024-07-24
- Publication Date
- 2025-03-18
AI Technical Summary
Existing carbon nanotube field-effect transistors (CNT-FETs) exhibit predominantly p-type semiconductor properties, limiting their application in logic circuits where high n-type semiconductor properties are required for improved operating speed and information processing.
A carbon nanotube composite is developed by attaching a conjugated polymer with specific repeating structural units to the surface of carbon nanotubes, enhancing their n-type semiconductor properties.
The carbon nanotube composite achieves high n-type semiconductor properties, leading to improved operating speed and information processing capabilities in logic circuits.
Smart Images

Figure 2025037798000018 
Figure 2025037798000019 
Figure 2025037798000020
Abstract
Description
[Technical field]
[0001] The present invention relates to a carbon nanotube composite, a semiconductor element using the same and a manufacturing method thereof, a circuit, a wireless communication device, a thin film transistor array, and a sensor. [Background technology]
[0002] In recent years, field-effect transistors (FETs) that use carbon nanotubes (CNTs), graphene, or organic semiconductors in the semiconductor layer and that can be applied with coating techniques such as inkjet technology and screen printing have been actively studied with the aim of realizing low-cost, large-area, flexible, and bendable electronic devices. Examples of electronic devices include displays, wireless communication devices using RFID (Radio Frequency IDentification) technology, and sensors, and FETs are used in the logic circuits and sensor parts of these IC chips.
[0003] FETs need to be made into p-type or n-type depending on their role, and the transistor characteristics need to be adjusted to balance this. For example, logic circuits in IC chips are generally constructed as complementary circuits consisting of p-type and n-type FETs to reduce power consumption.
[0004] It is known that FETs using CNTs (hereinafter referred to as CNT-FETs) usually exhibit the characteristics of a p-type semiconductor element in the atmosphere. Therefore, it has been considered to convert the characteristics of a CNT-FET to an n-type semiconductor element by forming a second insulating layer containing an organic compound containing a bond between carbon and nitrogen atoms or a second insulating layer containing a polymer having a specific functional group in part of the side chain on a semiconductor layer containing CNTs (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2017 / 130836 [Patent Document 2] International Publication No. 2019 / 097978 Summary of the Invention [Problem to be solved by the invention]
[0006] An important characteristic of logic circuits is their operating speed; the higher the operating speed, the faster the information processing speed and the better the device. To improve the operating speed, it is important to improve the characteristics of CNT-FETs, particularly the mobility. Although the techniques described in Patent Documents 1 and 2 disclose the mobility of n-type semiconductor elements, there is still room for improvement in order to further increase the mobility.
[0007] It is therefore an object of the present invention to provide a carbon nanotube composite and a semiconductor device that can achieve high n-type semiconductor characteristics. [Means for solving the problem]
[0008] That is, the present invention has the following configuration. [1] A carbon nanotube composite having a conjugated polymer attached to at least a portion of the surface of a carbon nanotube, the conjugated polymer having a repeating structural unit represented by the following general formula (1) or (2):
[0009] [ka]
[0010] [ka]
[0011] (In the general formula (1), X represents a structure represented by the general formula (3). 1represents an arylene group having 6 or more members or a heteroarylene group having 6 or more members, and represents a structure different from X. In general formula (2), X represents a structure represented by general formula (3). A 2 represents an arylene group having 6 or more members or a heteroarylene group having 6 or more members. B represents an ethenylene group, an ethynylene group, an arylene group, or a heteroarylene group. m represents an integer of 1 to 20. When two or more Bs are present, each B may be the same or different. A 2 and B may be the same or different from each other.)
[0012] [ka]
[0013] (In general formula (3), R 1 represents an alkyl group, an alkenyl group, an alkynyl group, an aryl group, a heteroaryl group, an alkoxy group, an aryloxy group, a heteroaryloxy group, an alkylsulfanyl group, an arylsulfanyl group, a heteroarylsulfanyl group, a halogen atom, a cyano group, a formyl group, a carbamoyl group, an amino group, an alkylcarbonyl group, an arylcarbonyl group, a heteroarylcarbonyl group, a carboxy group, an alkoxycarbonyl group, an aryloxycarbonyl group, a heteroaryloxycarbonyl group, an alkylcarbonyloxy group, an arylcarbonyloxy group, a heteroarylcarbonyloxy group, or a silyl group. R 2 ~R 4each independently represents a hydrogen atom, an alkyl group, an alkenyl group, an alkynyl group, an aryl group, a heteroaryl group, an alkoxy group, an aryloxy group, a heteroaryloxy group, an alkylsulfanyl group, an arylsulfanyl group, a heteroarylsulfanyl group, a halogen atom, a cyano group, a formyl group, a carbamoyl group, a mercapto group, an amino group, a nitro group, a nitroso group, a thionitroso group, an imino group, a sulfilimino group, an azo group, a diazo group, an alkylcarbonyl group, an arylcarbonyl group, a heteroarylcarbonyl group, a carboxy group, an alkoxycarbonyl group, an aryloxycarbonyl group, a heteroaryloxycarbonyl group, an alkylcarbonyloxy group, an arylcarbonyloxy group, a heteroarylcarbonyloxy group, or a silyl group. R 1 ~R 4 may be the same or different from each other. 3 and R 4 A ring structure may be formed by [2] R 1 is an alkyl group, an alkenyl group, an alkynyl group, an alkoxy group, an alkylsulfanyl group, a halogen atom, a cyano group, a formyl group, a carbamoyl group, an amino group, an alkylcarbonyl group, a carboxy group, an alkoxycarbonyl group, an alkylcarbonyloxy group, or a silyl group. [3] R 1 is an alkyl group having 3 carbon atoms or less, an alkenyl group having 3 carbon atoms or less, an alkynyl group having 3 carbon atoms or less, an alkoxy group having 2 carbon atoms or less, an alkylsulfanyl group having 2 carbon atoms or less, or a halogen atom. [4] R 3is an alkyl group, an alkenyl group, an alkynyl group, an aryl group, a heteroaryl group, an alkoxy group, an aryloxy group, a heteroaryloxy group, an alkylsulfanyl group, an arylsulfanyl group, a heteroarylsulfanyl group, a halogen atom, a cyano group, a formyl group, a carbamoyl group, a mercapto group, an amino group, a nitro group, a nitroso group, a thionitroso group, an imino group, a sulfilimino group, an azo group, a diazo group, an alkylcarbonyl group, an arylcarbonyl group, a heteroarylcarbonyl group, a carboxy group, an alkoxycarbonyl group, an aryloxycarbonyl group, a heteroaryloxycarbonyl group, an alkylcarbonyloxy group, an arylcarbonyloxy group, a heteroarylcarbonyloxy group, or a silyl group. [5] R 3 and R 4 The carbon nanotube composite according to any one of [1] to [4], wherein a ring structure is formed by [6] The carbon nanotube composite according to [5], wherein the ring structure is an aromatic ring or a heteroaromatic ring. [7] A semiconductor device comprising a substrate, a source electrode, a drain electrode and a gate electrode, a semiconductor layer in contact with the source electrode and the drain electrode, and a gate insulating layer insulating the semiconductor layer from the gate electrode, wherein the semiconductor layer contains the carbon nanotube composite according to any one of [1] to [6]. [8] The semiconductor element according to [7], further comprising a second insulating layer in contact with the semiconductor layer on the opposite side of the semiconductor layer from the gate insulating layer. [9] The semiconductor element according to [8], wherein the second insulating layer contains an electron-donating compound.
[10] A method for producing a semiconductor element according to any one of [7] to [9], comprising the step of forming the semiconductor layer by a coating method.
[11] A circuit comprising the semiconductor element according to any one of [7] to [9].
[12] A wireless communication device having at least the circuit according to
[11] and an antenna.
[13] A thin-film transistor array having the semiconductor element according to any one of [7] to [9].
[14] A sensor comprising the semiconductor element according to any one of [7] to [9]. Effect of the Invention
[0014] According to the present invention, it is possible to obtain a carbon nanotube composite and a semiconductor element that can realize high n-type semiconductor characteristics. It is also possible to provide a circuit, a wireless communication device, a thin film transistor array, and a sensor that utilize the carbon nanotube composite and the semiconductor element that uses the same. [Brief description of the drawings]
[0015] [Figure 1] Schematic cross-sectional view showing an example of the configuration of a semiconductor element. [Diagram 2] Schematic cross-sectional view showing an example of the configuration of a semiconductor element. [Diagram 3] Schematic cross-sectional view showing an example of the configuration of a semiconductor element. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, preferred embodiments of the carbon nanotube composite according to the present invention, the semiconductor element and its manufacturing method, the circuit, the wireless communication device, the thin film transistor array, and the sensor using the same will be described in detail. However, the present invention is not limited to the following embodiments, and can be modified in various ways depending on the purpose and application.
[0017] <Carbon nanotube composite> In the present invention, a carbon nanotube (hereinafter, referred to as CNT) composite refers to a CNT having a conjugated polymer having a repeating structural unit represented by the general formula (1) or (2) described below attached to at least a part of the surface of the CNT.
[0018] By attaching a conjugated polymer to at least a portion of the CNT surface, it becomes possible to uniformly disperse the CNT in a solution without impairing the high electrical properties of the CNT. If a solution in which CNTs are uniformly dispersed is used, it becomes possible to form a uniformly dispersed CNT film by a coating method. This makes it possible to realize high semiconducting properties.
[0019] The state where a conjugated polymer is attached to at least a part of the surface of a CNT means that a part or the whole of the surface of the CNT is covered with the conjugated polymer. It is presumed that the reason why a conjugated polymer can cover a CNT is that the π-electron clouds derived from the conjugated structures of both polymers overlap, causing an interaction.
[0020] Whether or not a CNT is coated with a conjugated polymer can be determined from the reflected color of the CNT. The reflected color of coated CNT is different from that of uncoated CNT and is close to that of the conjugated polymer. Quantitatively, the presence of a deposit on the CNT can be confirmed and the weight ratio of the deposit to the CNT can be measured by elemental analysis such as X-ray photoelectron spectroscopy (XPS). The conjugated polymer preferably coats 5% to 90% of the surface of the CNT, more preferably 70% or less, and even more preferably 50% or less.
[0021] Methods for attaching a conjugated polymer to CNT include (I) a method of adding CNT to a molten conjugated polymer and mixing it, (II) a method of dissolving a conjugated polymer in a solvent, adding CNT to the solution, and mixing it, (III) a method of preliminarily dispersing CNT in a solvent using ultrasonic waves or the like, adding a conjugated polymer thereto, and mixing it, and (IV) a method of putting a conjugated polymer and CNT in a solvent, irradiating the mixture with ultrasonic waves, and mixing them, etc. In the present invention, any of these methods may be used, or a combination of multiple methods may be used.
[0022] (CNT) As the CNT, any of the following may be used: single-walled CNT, in which one carbon film (graphene sheet) is wound in a cylindrical shape; double-walled CNT, in which two graphene sheets are wound concentrically; and multi-walled CNT, in which multiple graphene sheets are wound concentrically. In order to obtain high semiconductor properties, it is preferable to use single-walled CNT. CNT can be obtained by the arc discharge method, the chemical vapor deposition method (CVD method), the laser ablation method, etc.
[0023] Moreover, it is more preferable that the CNT contains 80% by weight or more of semiconducting CNT. More preferably, it contains 90% by weight or more of semiconducting CNT, and particularly preferably, it contains 95% by weight or more of semiconducting CNT. As a method for making CNT contain 80% by weight or more of semiconducting CNT, a known method can be used. For example, there are a method of ultracentrifugation in the presence of a density gradient agent, a method of selectively attaching a specific compound to the surface of semiconducting or metallic CNT and separating them by utilizing the difference in solubility, and a method of separating them by electrophoresis or the like by utilizing the difference in electrical properties. As a method for measuring the content of semiconducting CNT in CNT, there are a method of calculating from the absorption area ratio of visible-near infrared absorption spectrum, a method of calculating from the intensity ratio of Raman spectrum, and the like.
[0024] In the present invention, when CNTs are used in the semiconductor layer of a semiconductor element, the length of the CNTs is preferably shorter than the distance between the source electrode and the drain electrode (hereinafter, "electrode distance"). The average length of the CNTs is preferably 2 μm or less, more preferably 1 μm or less, depending on the electrode distance. Methods for shortening the length of the CNTs include acid treatment and freeze-pulverization treatment.
[0025] The average length of CNTs refers to the average length of 20 randomly picked CNTs. One method for measuring the average length of CNTs is to randomly pick up 20 CNTs from images obtained using an atomic force microscope, scanning electron microscope, transmission electron microscope, etc., and calculate the average length of these.
[0026] Generally, commercially available CNTs have a distribution in length, and may contain CNTs longer than the distance between the electrodes. Therefore, it is preferable to add a process to make the CNTs shorter than the distance between the electrodes. For example, a method of cutting the CNTs into short fibers by acid treatment with nitric acid, sulfuric acid, or the like, ultrasonic treatment, or freeze-pulverization is effective. In addition, it is more preferable to use separation by a filter in order to improve the purity of the CNTs.
[0027] Furthermore, the diameter of the CNT is not particularly limited, but is preferably from 1 nm to 100 nm, and more preferably has an upper limit of 50 nm.
[0028] In the present invention, it is preferable to provide a process of uniformly dispersing CNTs in a solvent and filtering the dispersion through a filter. By obtaining CNTs smaller than the filter pore size from the filtrate, CNTs shorter than the distance between the electrodes can be efficiently obtained. In this case, a membrane filter is preferably used as the filter. The pore size of the filter used for filtration should be smaller than the distance between the electrodes, and is preferably 0.5 to 10 μm.
[0029] (Conjugated polymer) In the present invention, the conjugated polymer has a repeating structural unit represented by the following general formula (1) or (2). In this conjugated polymer, X and A 1 Due to the magnitude of steric hindrance around the bond, the plane of the aromatic ring represented by X and A 1 The dihedral angle with the plane formed by the aromatic ring or heteroaromatic ring, represented by X, becomes larger. When the dihedral angle becomes larger in this way, the effective conjugation length of the main chain of the conjugated polymer becomes shorter. When the effective conjugation length becomes shorter, the LUMO level that accepts electrons becomes shallower, making it difficult to accept electrons. As a result, electrons flowing through the CNT are less likely to be trapped by the conjugated polymer, resulting in a CNT composite in which electrons flow more easily. It is believed that this makes it possible to obtain a carbon nanotube composite that can achieve high n-type semiconductor properties. X and A 2 A similar mechanism is thought to be involved in the relationship between
[0030] [ka]
[0031] [ka]
[0032] In the general formula (1), X represents a structure represented by the general formula (3). 1 represents an arylene group having 6 or more members or a heteroarylene group having 6 or more members, and represents a structure different from X. In general formula (2), X represents a structure represented by general formula (3). A 2 represents an arylene group having 6 or more members or a heteroarylene group having 6 or more members. B represents an ethenylene group, an ethynylene group, an arylene group, or a heteroarylene group. m represents an integer of 1 to 20. When two or more Bs are present, each B may be the same or different. A 2 and B may be the same or different from each other.
[0033] [ka]
[0034] In general formula (3), R 1 represents an alkyl group, an alkenyl group, an alkynyl group, an aryl group, a heteroaryl group, an alkoxy group, an aryloxy group, a heteroaryloxy group, an alkylsulfanyl group, an arylsulfanyl group, a heteroarylsulfanyl group, a halogen atom, a cyano group, a formyl group, a carbamoyl group, an amino group, an alkylcarbonyl group, an arylcarbonyl group, a heteroarylcarbonyl group, a carboxy group, an alkoxycarbonyl group, an aryloxycarbonyl group, a heteroaryloxycarbonyl group, an alkylcarbonyloxy group, an arylcarbonyloxy group, a heteroarylcarbonyloxy group, or a silyl group. R 2 ~R 4each independently represents a hydrogen atom, an alkyl group, an alkenyl group, an alkynyl group, an aryl group, a heteroaryl group, an alkoxy group, an aryloxy group, a heteroaryloxy group, an alkylsulfanyl group, an arylsulfanyl group, a heteroarylsulfanyl group, a halogen atom, a cyano group, a formyl group, a carbamoyl group, a mercapto group, an amino group, a nitro group, a nitroso group, a thionitroso group, an imino group, a sulfilimino group, an azo group, a diazo group, an alkylcarbonyl group, an arylcarbonyl group, a heteroarylcarbonyl group, a carboxy group, an alkoxycarbonyl group, an aryloxycarbonyl group, a heteroaryloxycarbonyl group, an alkylcarbonyloxy group, an arylcarbonyloxy group, a heteroarylcarbonyloxy group, or a silyl group. R 1 ~R 4 may be the same or different from each other. 3 and R 4 A ring structure may be formed by:
[0035] In the present invention, the conjugated polymer refers to a compound in which the repeating unit has a conjugated structure and the degree of polymerization is 2 or more.
[0036] The arylene group refers to a divalent aromatic hydrocarbon group consisting of a single ring or a condensed ring, and examples thereof include a phenylene group, a naphthylene group, a phenanthrylene group, an anthrylene group, a pyrenylene group, a fluorenylene group, and a perylenylene group. The arylene group may be unsubstituted or substituted. The number of carbon atoms in the arylene group is not particularly limited, but is preferably in the range of 6 to 40.
[0037] The heteroarylene group refers to a divalent heteroaromatic ring group consisting of a single ring or a condensed ring, and examples thereof include pyridylene group, pyrazylene group, quinolinylene group, isoquinolylene group, quinoxalylene group, acridinylene group, indolylene group, carbazolylene group, and the like, as well as divalent groups derived from heteroaromatic rings such as benzofuran, dibenzofuran, benzothiophene, dibenzothiophene, benzodithiophene, benzothiadiazole, benzosilole, and dibenzosilole. The heteroarylene group may be unsubstituted or substituted. The number of carbon atoms in the heteroarylene group is not particularly limited, but is preferably in the range of 2 to 30.
[0038] The alkyl group refers to a saturated aliphatic hydrocarbon group such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, or a tert-butyl group. The alkyl group may or may not have a substituent, and may be a chain or a ring. The number of carbon atoms in the alkyl group is not particularly limited, but is preferably 1 to 20, more preferably 1 to 8, from the viewpoints of availability and cost.
[0039] The alkenyl group refers to an unsaturated aliphatic hydrocarbon group such as an ethenyl group, a propenyl group, a butenyl group, or a hexenyl group. The alkenyl group may or may not have a substituent, and may be a chain or a ring. The number of carbon atoms in the alkenyl group is not particularly limited, but is preferably 2 to 20, more preferably 2 to 8, from the viewpoints of availability and cost.
[0040] The alkynyl group refers to an unsaturated aliphatic hydrocarbon group such as an ethynyl group, a propynyl group, a butynyl group, or a hexynyl group. The alkynyl group may or may not have a substituent, and may be a chain or a ring. The number of carbon atoms in the alkynyl group is not particularly limited, but is preferably 2 to 20, more preferably 2 to 8, from the viewpoint of availability and cost.
[0041] The aryl group refers to a monovalent aromatic hydrocarbon group, and examples thereof include a phenyl group, a naphthyl group, an anthracenyl group, a phenanthryl group, a pyrenyl group, and a fluorenyl group. The aryl group may or may not have a substituent. The number of carbon atoms in the aromatic hydrocarbon group is not particularly limited, but is preferably in the range of 6 to 40.
[0042] The heteroaryl group refers to a monovalent heteroaromatic ring group, such as a furanyl group, a thiophenyl group, a benzofuranyl group, a dibenzofuranyl group, a pyridyl group, a quinolinyl group, a benzosilole group, a dibenzosilole group, etc., which refers to an aromatic group having one or more atoms other than carbon atoms in the ring. The heteroaryl group may or may not have a substituent. The number of carbon atoms in the heteroaryl group is not particularly limited, but is preferably in the range of 2 to 30.
[0043] The alkoxy group refers to a functional group in which one side of an ether bond is substituted with an alkyl group, such as a methoxy group, an ethoxy group, or a propoxy group. The alkoxy group may or may not have a substituent. The number of carbon atoms in the alkoxy group is not particularly limited, but is preferably in the range of 1 to 20.
[0044] The aryloxy group refers to a functional group in which one side of an ether bond is replaced with an aryl group, such as a phenoxy group or a naphthoxy group. The aryloxy group may or may not have a substituent. The number of carbon atoms in the aryloxy group is not particularly limited, but is preferably in the range of 6 to 40.
[0045] The heteroaryloxy group refers to a functional group in which one side of an ether bond is replaced with a heteroaryl group. The heteroaryloxy group may or may not have a substituent. The number of carbon atoms in the heteroaryloxy group is not particularly limited, but is preferably in the range of 2 to 30.
[0046] The alkylsulfanyl group refers to a functional group in which one side of a sulfanyl group is substituted with an alkyl group, such as a methylsulfanyl group, an ethylsulfanyl group, or an n-propylsulfanyl group. The alkylsulfanyl group may or may not have a substituent. The number of carbon atoms in the alkylsulfanyl group is not particularly limited, but is preferably in the range of 2 to 20.
[0047] The arylsulfanyl group refers to a functional group in which one side of a sulfanyl group is replaced with an aryl group, such as a phenylsulfanyl group or a naphthylsulfanyl group. The arylsulfanyl group may or may not have a substituent. The number of carbon atoms in the arylsulfanyl group is not particularly limited, but is preferably in the range of 2 to 20.
[0048] The heteroarylsulfanyl group refers to a functional group in which one side of a sulfanyl group is replaced with a heteroaryl group, such as a furanylsulfanyl group or a thiophenylsulfanyl group. The heteroarylsulfanyl group may or may not have a substituent. The number of carbon atoms in the heteroarylsulfanyl group is not particularly limited, but is preferably in the range of 2 to 20.
[0049] The alkylcarbonyl group refers to a functional group in which one side of a carbonyl bond is substituted with an alkyl group, such as an acetyl group or a hexanoyl group. The alkylcarbonyl group may or may not have a substituent. The number of carbon atoms in the alkylcarbonyl group is not particularly limited, but is preferably in the range of 2 to 20.
[0050] The arylcarbonyl group refers to a functional group in which one side of a carbonyl bond is replaced with an aryl group, such as a benzoyl group. The arylcarbonyl group may or may not have a substituent. The number of carbon atoms in the arylcarbonyl group is not particularly limited, but is preferably in the range of 6 to 40.
[0051] The heteroarylcarbonyl group refers to a functional group in which one side of a carbonyl bond is replaced with a heteroaryl group. The heteroarylcarbonyl group may or may not have a substituent. The number of carbon atoms in the heteroarylcarbonyl group is not particularly limited, but is preferably in the range of 2 to 30.
[0052] The alkoxycarbonyl group refers to a functional group in which one side of a carbonyl bond is replaced with an alkoxy group, such as a methoxycarbonyl group. The alkoxycarbonyl group may or may not have a substituent. The number of carbon atoms in the alkoxycarbonyl group is not particularly limited, but is preferably in the range of 2 to 20.
[0053] The aryloxycarbonyl group refers to a functional group in which one side of a carbonyl bond is replaced with an aryloxy group, such as a phenoxycarbonyl group. The aryloxycarbonyl group may or may not have a substituent. The number of carbon atoms in the aryloxycarbonyl group is not particularly limited, but is preferably in the range of 6 to 40.
[0054] The heteroaryloxycarbonyl group refers to a functional group in which one side of a carbonyl bond is replaced with a heteroaryloxy group. The heteroaryloxycarbonyl group may or may not have a substituent. The number of carbon atoms in the heteroaryloxycarbonyl group is not particularly limited, but is preferably in the range of 2 to 30.
[0055] The alkylcarbonyloxy group refers to a functional group in which one side of an ether bond is replaced with an alkylcarbonyl group, such as an acetoxy group. The alkylcarbonyloxy group may or may not have a substituent. The number of carbon atoms in the alkylcarbonyloxy group is not particularly limited, but is preferably in the range of 2 to 20.
[0056] The arylcarbonyloxy group refers to a functional group in which one side of an ether bond is replaced with an arylcarbonyl group, such as a benzoyloxy group. The arylcarbonyloxy group may or may not have a substituent. The number of carbon atoms in the arylcarbonyloxy group is not particularly limited, but is preferably in the range of 6 to 40.
[0057] The heteroarylcarbonyloxy group refers to a functional group in which one side of an ether bond is replaced with a heteroarylcarbonyl group. The heteroarylcarbonyloxy group may or may not have a substituent. The number of carbon atoms in the arylcarbonyloxy group is not particularly limited, but is preferably in the range of 2 to 30.
[0058] From the viewpoint of improving semiconductor properties by increasing CNT dispersibility, 1 is preferably a substituent having a moderate degree of steric hindrance. This is because the main chain of a conjugated polymer can disperse CNTs by interacting with the CNTs, but R 1 As the steric hindrance of R increases, 1 This is because the main chain portion of the conjugated polymer that can come into contact with the CNTs becomes smaller, and the interactivity of the conjugated polymer with the CNTs decreases.
[0059] R 1 Specifically, is preferably an alkyl group, an alkenyl group, an alkynyl group, an alkoxy group, an alkylsulfanyl group, a halogen atom, a cyano group, a formyl group, a carbamoyl group, an amino group, an alkylcarbonyl group, a carboxy group, an alkoxycarbonyl group, an alkylcarbonyloxy group, or a silyl group, and more preferably an alkyl group having 3 or less carbon atoms, an alkenyl group having 3 or less carbon atoms, an alkynyl group having 3 or less carbon atoms, an alkoxy group having 2 or less carbon atoms, an alkylsulfanyl group having 2 or less carbon atoms, or a halogen atom.
[0060] R 1is more preferably a halogen atom. As described above, this is because halogen atoms are substituents with moderate steric hindrance, and CNTs become negatively charged when they pass electrons, but the electron-withdrawing properties of halogen atoms stabilize the positively charged main chain of the conjugated polymer, improving the electron passing ability of CNTs, i.e., their properties as n-type semiconductors. It is particularly preferable that the halogen atom is a fluorine atom.
[0061] In order to suppress electron trapping by the conjugated polymer, the above R 3 is preferably an alkyl group, an alkenyl group, an alkynyl group, an aryl group, a heteroaryl group, an alkoxy group, an aryloxy group, a heteroaryloxy group, an alkylsulfanyl group, an arylsulfanyl group, a heteroarylsulfanyl group, a halogen atom, a cyano group, a formyl group, a carbamoyl group, a mercapto group, an amino group, a nitro group, a nitroso group, a thionitroso group, an imino group, a sulfilimino group, an azo group, a diazo group, an alkylcarbonyl group, an arylcarbonyl group, a heteroarylcarbonyl group, a carboxy group, an alkoxycarbonyl group, an aryloxycarbonyl group, a heteroaryloxycarbonyl group, an alkylcarbonyloxy group, an arylcarbonyloxy group, a heteroarylcarbonyloxy group, or a silyl group. 1 Since the steric hindrance around the bond of X becomes larger, the dihedral angle tends to become larger, and the effective conjugation length of the main chain of the conjugated polymer becomes shorter, so that the conjugated polymer is less likely to trap electrons. This can further enhance the above-mentioned effect. 2 The relationship between the two is thought to involve a similar mechanism.
[0062] R 3Specifically, is preferably an alkyl group, an alkenyl group, an alkynyl group, an alkoxy group, an alkylsulfanyl group, a halogen atom, a cyano group, a formyl group, a carbamoyl group, an amino group, a nitro group, a nitroso group, a thionitroso group, an imino group, a sulfilimino group, azo group, a diazo group, an alkylcarbonyl group, a carboxy group, an alkoxycarbonyl group, an alkylcarbonyloxy group, or a silyl group, and more preferably an alkyl group having 3 or less carbon atoms, an alkenyl group having 3 or less carbon atoms, an alkynyl group having 3 or less carbon atoms, an alkoxy group having 2 or less carbon atoms, an alkylsulfanyl group having 2 or less carbon atoms, or a halogen atom.
[0063] R 2 and R 4 is not particularly limited as long as it is the above-mentioned group, but in terms of ease of monomer synthesis and polymerization reaction, it is preferably an alkyl group having 6 or less carbon atoms, an alkenyl group having 6 or less carbon atoms, an alkynyl group having 6 or less carbon atoms, an alkoxy group having 6 or less carbon atoms, an alkylsulfanyl group having 6 or less carbon atoms, or a halogen atom, and more preferably an alkyl group having 3 or less carbon atoms, an alkenyl group having 3 or less carbon atoms, an alkynyl group having 3 or less carbon atoms, an alkoxy group having 3 or less carbon atoms, an alkylsulfanyl group having 3 or less carbon atoms, or a halogen atom.
[0064] From the viewpoint of improving semiconductor properties by increasing CNT dispersibility, 3 and R 4 It is preferable that a ring structure is formed by the above. This is because the adsorption force of the conjugated polymer to the CNT is strengthened, and the CNT dispersibility is improved. The ring structure may be a saturated ring or an unsaturated ring. More preferably, the ring structure is an aromatic ring or a heteroaromatic ring. This further improves the CNT dispersibility.
[0065] R 3 and R 4Examples of the aromatic ring or heteroaromatic ring formed by the formula (I) include a benzene ring, a furan ring, a thiophene ring, a pyrrole ring, an imidazole ring, an oxazole ring, a thiazole ring, a pyridazine ring, a pyrimidine ring, a pyrazine ring, and a thiadiazole ring.
[0066] A 1 and A 2 represents an arylene group having six or more members or a heteroarylene group having six or more members, which is because the above-mentioned steric hindrance around the bond has a large effect of suppressing electron trapping.
[0067] Also, A 1 , A 2 and B are preferably divalent aromatic hydrocarbon groups or heteroaromatic ring groups consisting of condensed rings. This allows the conjugated polymer to adhere to the CNTs more easily, improving CNT dispersibility and semiconductor properties. Examples of the condensed ring include a naphthalene ring, an anthracene ring, a pyrene ring, a perylene ring, a quinoline ring, a quinoxaline ring, a fluorene ring, a carbazole ring, and a silafluorene ring, with the fluorene ring, carbazole ring, and silafluorene ring being preferred, and the fluorene ring and silafluorene ring being more preferred.
[0068] m represents an integer of 1 to 20, preferably 1 to 10, and more preferably 1 to 5, in terms of ease of monomer synthesis and polymerization reaction.
[0069] Specific examples of the conjugated polymer preferably used in the present invention include those having the following repeating structural units, but are not limited thereto.
[0070] [ka]
[0071] [ka]
[0072] [ka]
[0073] [ka]
[0074] [ka]
[0075] The conjugated polymer can be synthesized by a known method, for example, a method in which a monomer having a terminal bromo group and a monomer having a terminal boronic acid, a boronic acid ester, or a trialkyltin group such as a trimethyltin group are coupled in the presence of a palladium catalyst.
[0076] It is preferable to use a conjugated polymer from which impurities such as raw materials and by-products used in the synthesis process have been removed. Methods for removing impurities include, for example, silica gel columnography, Soxhlet extraction, filtration, ion exchange, and chelate methods. Two or more of these methods may be combined.
[0077] <Semiconductor element> A semiconductor element according to an embodiment of the present invention is a semiconductor element including a substrate, a source electrode, a drain electrode, and a gate electrode, a semiconductor layer in contact with the source electrode and the drain electrode, and a gate insulating layer that insulates the semiconductor layer from the gate electrode, wherein the semiconductor layer contains a CNT complex having a conjugated polymer having a repeating structural unit represented by the general formula (1) or (2) attached to at least a portion of the surface of the CNT.
[0078] 1 is a schematic cross-sectional view showing a first example of a semiconductor device according to an embodiment of the present invention. The semiconductor device has a gate electrode 2 formed on an insulating substrate 1, a gate insulating layer 3 covering the gate electrode 2, a source electrode 5 and a drain electrode 6 provided thereon, and a semiconductor layer 4 provided between the electrodes. The semiconductor layer 4 includes a CNT composite 7.
[0079] This structure is a so-called bottom-gate bottom-contact structure in which a gate electrode is disposed below a semiconductor layer, and a source electrode and a drain electrode are disposed on the lower surface of the semiconductor layer.
[0080] 2 is a schematic cross-sectional view showing a second example of a semiconductor device according to an embodiment of the present invention. The semiconductor device has a gate electrode 2 formed on an insulating base material 1, a gate insulating layer 3 covering the gate electrode 2, a semiconductor layer 4 provided thereon, and a source electrode 5 and a drain electrode 6 formed thereon. The semiconductor layer 4 includes a CNT composite 7.
[0081] This structure is a so-called bottom-gate top-contact structure in which a gate electrode is disposed under a semiconductor layer, and a source electrode and a drain electrode are disposed on an upper surface of the semiconductor layer.
[0082] The structure of the semiconductor element according to the embodiment of the present invention is not limited to these, and the following description is common regardless of the structure of the semiconductor element unless otherwise specified.
[0083] (Semiconductor layer) The semiconductor layer contains the CNT hybrid material of the present invention. The semiconductor layer may further contain an organic semiconductor or an insulating material as long as the electrical properties are not impaired.
[0084] The thickness of the semiconductor layer is preferably 1 nm or more and 100 nm or less. Within this range, it is easy to form a uniform thin film. The thickness of the semiconductor layer is more preferably 1 nm or more and 50 nm or less, and further preferably 1 nm or more and 20 nm or less. The thickness can be measured by an atomic force microscope, an ellipsometry method, or the like.
[0085] As a method for forming the semiconductor layer, a dry method such as resistance heating deposition, electron beam, sputtering, and CVD can be used, but from the viewpoint of manufacturing cost and compatibility with large areas, it is preferable to use a coating method. Specifically, a spin coating method, a blade coating method, a slit die coating method, a screen printing method, a bar coater method, a mold method, a print transfer method, a dip and pull method, an inkjet method, and the like can be preferably used. Among these, it is preferable to select a coating method according to the coating film properties to be obtained, such as coating film thickness control and orientation control. Among them, for the above-mentioned reasons, inkjet coating is particularly preferable for circuit formation. In addition, the formed coating film may be annealed under air, reduced pressure, or in an inert gas atmosphere such as nitrogen or argon.
[0086] (Second insulating layer) The semiconductor device according to the embodiment of the present invention preferably further comprises a second insulating layer. The second insulating layer is formed on the semiconductor layer on the opposite side to the gate insulating layer. The opposite side to the gate insulating layer on the semiconductor layer refers to the upper side of the semiconductor layer, for example, when the gate insulating layer is formed on the lower side of the semiconductor layer. By forming the second insulating layer, the characteristics of the n-type semiconductor device can be improved.
[0087] 3 is a schematic cross-sectional view showing a third example of a semiconductor device according to an embodiment of the present invention. The semiconductor device has a gate electrode 2 formed on an insulating base material 1, a gate insulating layer 3 covering the gate electrode 2, a source electrode 5 and a drain electrode 6 provided thereon, a semiconductor layer 4 provided between these electrodes, and a second insulating layer 8 covering the semiconductor layer. The semiconductor layer 4 includes a CNT complex 7.
[0088] Materials used for the second insulating layer are not particularly limited, but specific examples include inorganic materials such as silicon oxide and alumina; organic polymer materials such as polyimide and its derivatives, polyvinyl alcohol, polyvinyl chloride, polyethylene terephthalate, polyvinylidene fluoride, polyacrylonitrile, polysiloxane and its derivatives, polyvinylphenol and its derivatives, polynorbornene, polystyrene, polycarbonate and their derivatives, polyacrylic acid derivatives, and polymethacrylic acid derivatives; or mixtures of inorganic material powders and organic polymer materials, and mixtures of organic low molecular weight materials and organic polymer materials.
[0089] The second insulating layer preferably contains an electron donating compound. Electron donating refers to the ability of a compound to donate electrons to another compound, and an electron donating compound is a compound that has the ability to donate electrons. By containing the electron donating compound in the second insulating layer, the characteristics of the n-type semiconductor device can be further improved.
[0090] Examples of the electron donating compound include compounds having a phosphorus atom, a nitrogen atom, or a sulfur atom, such as amide compounds, imide compounds, urea compounds, amine compounds, imine compounds, aniline compounds, nitrile compounds, alkylphosphine compounds, sulfur-containing heterocyclic compounds, etc. Among these, sulfur-containing heterocyclic compounds and amine compounds are preferred.
[0091] The thickness of the second insulating layer is preferably 50 nm or more, more preferably 100 nm or more, and the upper limit of the thickness of the second insulating layer is not particularly limited, but is preferably 1 mm or less, more preferably 100 μm or less. The second insulating layer may be a single layer or multiple layers, and one layer may be formed from multiple insulating materials, or multiple insulating materials may be laminated.
[0092] The film thickness of the second insulating layer is determined by measuring a cross section of the second insulating layer using a scanning electron microscope, calculating the film thickness at 10 points randomly selected from the portion of the second insulating layer located on the semiconductor layer in the obtained image, and calculating the arithmetic average value.
[0093] The method for forming the second insulating layer is not particularly limited, and a dry method such as resistance heating deposition, electron beam, sputtering, or CVD can be used, but a coating method is preferably used from the viewpoint of production cost and suitability for large areas. The coating method includes at least a step of coating a composition in which a material for forming the second insulating layer is dissolved.
[0094] The formed coating film may be subjected to annealing or hot air drying in air, under reduced pressure, or in an inert gas atmosphere such as nitrogen or argon.
[0095] Specific examples of the second insulating layer include the second insulating layers described in WO 2018 / 180146, WO 2019 / 097978, WO 2020 / 195707, and WO 2020 / 195708.
[0096] (base material) The substrate may be made of any material as long as at least the surface on which the electrode system is disposed is an insulating substrate. As the substrate, for example, substrates made of inorganic materials such as silicon wafers, glass, sapphire, and sintered alumina, and substrates made of organic materials such as polyimide, polyvinyl alcohol, polyvinyl chloride, polyethylene terephthalate, polyvinylidene fluoride, polysiloxane, polyvinylphenol (PVP), polyester, polycarbonate, polysulfone, polyethersulfone, polyethylene, polyphenylene sulfide, and polyparaxylene are preferable.
[0097] The substrate may also be a laminate of multiple materials, such as a PVP film formed on a silicon wafer or a polysiloxane film formed on polyethylene terephthalate.
[0098] (electrode) The materials used for the gate electrode, source electrode, and drain electrode may be any conductive material that can be generally used as an electrode. For example, conductive metal oxides such as tin oxide, indium oxide, and indium tin oxide (ITO) are included; metals such as platinum, gold, silver, copper, iron, tin, zinc, aluminum, indium, chromium, lithium, sodium, potassium, cesium, calcium, magnesium, palladium, molybdenum, amorphous silicon, and polysilicon, and alloys thereof; inorganic conductive materials such as copper iodide and copper sulfide; polythiophene, polypyrrole, and polyaniline; complexes of polyethylenedioxythiophene and polystyrene sulfonic acid; conductive polymers whose conductivity is improved by doping with iodine, etc.; carbon materials; and materials containing organic components and conductors, but are not limited thereto.
[0099] These electrode materials may be used alone, or a plurality of materials may be laminated or mixed for use.
[0100] Among these, it is preferable that the electrode contains an organic component and a conductor, since this increases the flexibility of the electrode, provides good adhesion to the substrate and the gate insulating layer even when bent, and provides good electrical connection with the wiring and the semiconductor layer.
[0101] The organic component is not particularly limited, and examples thereof include monomers, oligomers, polymers, photopolymerization initiators, plasticizers, leveling agents, surfactants, silane coupling agents, defoamers, pigments, etc. From the viewpoint of improving the bending resistance of the electrode, the organic component is preferably an oligomer or a polymer.
[0102] The conductor may be any conductive material that can be generally used as an electrode, but is preferably a conductive particle.
[0103] Examples of the conductive particles include gold, silver, copper, nickel, tin, bismuth, lead, zinc, palladium, platinum, aluminum, tungsten, molybdenum, and carbon. More preferred TEPCO commutators are conductive particles containing at least one element selected from the group consisting of gold, silver, copper, nickel, tin, bismuth, lead, zinc, palladium, platinum, aluminum, and carbon. These conductive particles may be used alone, as an alloy, or as a mixed particle.
[0104] Among these, gold, silver, copper or platinum particles are preferred from the viewpoint of electrical conductivity, and silver particles are more preferred from the viewpoints of cost and stability.
[0105] The width and thickness of each of the gate electrode, source electrode, and drain electrode, and the distance between the source electrode and the drain electrode can be designed to any value. For example, the electrode width is preferably 10 μm to 10 mm, the electrode thickness is preferably 0.01 μm to 100 μm, and the distance between the source electrode and the drain electrode is preferably 1 μm to 1 mm, but is not limited to these.
[0106] The method for forming the electrode is not particularly limited, and examples thereof include methods using known techniques such as resistance heating deposition, electron beam, sputtering, plating, CVD, ion plating coating, inkjet, printing, etc. Another example of the method for forming the electrode includes a method in which a paste containing an organic component and a conductor is applied onto an insulating substrate by known techniques such as spin coating, blade coating, slit die coating, screen printing, bar coater, casting, printing transfer, and immersion and pulling, and then dried using an oven, a hot plate, infrared rays, or the like to form the electrode.
[0107] As a method for forming an electrode pattern, the electrode thin film prepared by the above method may be patterned into a desired shape by a known photolithography method or the like, or a pattern may be formed by using a mask of a desired shape during vapor deposition or sputtering of an electrode material.
[0108] (Gate insulation layer) The material used for the gate insulating layer is not particularly limited as long as it ensures insulation between the semiconductor layer and the gate electrode, and examples of the material include inorganic materials such as silicon oxide and alumina; organic polymer materials such as polyimide, polyvinyl alcohol, polyvinyl chloride, polyethylene terephthalate, polyvinylidene fluoride, polysiloxane, and polyvinylphenol (PVP); and mixtures of inorganic material powders and organic materials.
[0109] Among these, those containing organic compounds containing silicon-carbon bonds are preferred, with polysiloxanes being particularly preferred.
[0110] The gate insulating layer preferably further contains a metal compound containing a bond between a metal atom and an oxygen atom. Such a metal compound is not particularly limited, and examples thereof include metal oxides and metal hydroxides. The metal atom contained in the metal compound may form a metal chelate. Examples of the metal atom include magnesium, aluminum, titanium, chromium, manganese, cobalt, nickel, copper, zinc, gallium, zirconium, ruthenium, palladium, indium, hafnium, and platinum. Among them, aluminum is preferred in terms of availability, cost, and stability of the metal chelate. Examples of the metal oxide include silicon oxide, titanium oxide, zirconium oxide, hafnium oxide, tin oxide, barium titanate, strontium titanate, and calcium titanate. The metal compound may also be in the form of particles.
[0111] The thickness of the gate insulating layer is preferably 0.05 μm to 5 μm, and more preferably 0.1 μm to 1 μm. By setting the thickness within this range, it becomes easy to form a uniform thin film. The thickness can be measured by an atomic force microscope, an ellipsometry method, or the like.
[0112] The gate insulating layer may be a single layer or multiple layers. In addition, one layer may be formed from multiple insulating materials, or multiple insulating materials may be stacked to form multiple insulating layers.
[0113] In a circuit, when it is necessary to electrically connect a source electrode or a drain electrode to a gate electrode, a via may be formed in the gate insulating layer. Examples of a method for forming a via include a method for forming a via by laser processing, a method for directly forming a required pattern by screen printing or offset printing, and a method for processing by photolithography. When processing by photolithography, it is preferable that the gate insulating layer has photosensitivity. The photosensitivity may be either positive type or negative type.
[0114] Specific examples of the gate insulating layer include the gate insulating layers described in WO 2018 / 097042 and WO 2019 / 065561.
[0115] (protective layer) The semiconductor element may further have a protective layer on the semiconductor layer, the second insulating layer, etc. The role of the protective layer is to protect the semiconductor element from physical damage such as rubbing and from moisture and oxygen in the air.
[0116] Examples of the material of the protective layer include inorganic materials such as silicon wafer, glass, sapphire, and alumina sintered body, and organic materials such as polyimide, polyvinyl alcohol, polyvinyl chloride, polyethylene terephthalate, polyvinylidene fluoride, polysiloxane, polyvinylphenol, polyester, polycarbonate, polysulfone, polyethersulfone, polyethylene, polyphenylene sulfide, polyparaxylene, polyacrylonitrile, and cycloolefin polymer. In addition, the protective layer may be a laminate of a plurality of materials, such as a polyvinylphenol film formed on a silicon wafer or an aluminum oxide film formed on polyethylene terephthalate. In addition, the above materials may be bonded together with an adhesive layer or a pressure-sensitive adhesive layer.
[0117] <Evaluation of semiconductor device characteristics> In the semiconductor device according to the embodiment of the present invention, the current flowing between the source electrode and the drain electrode (source-drain current) can be controlled by changing the gate voltage. 2 / V s) can be calculated using the following formula (a).
[0118] μ=(δId / δVg)L·D / (W·εr·ε·Vsd) (a) where Id is the source-drain current (A), Vsd is the source-drain voltage (V), Vg is the gate voltage (V), D is the thickness of the gate insulating layer (m), L is the channel length (m), W is the channel width (m), εr is the relative dielectric constant of the gate insulating layer (F / m), and ε is the dielectric constant of vacuum (8.85×10 -12 F / m), and δ indicates the change in the corresponding physical quantity.
[0119] An n-type semiconductor element operates by applying a positive voltage to the gate electrode, providing electrical continuity between the source and drain. An n-type semiconductor element with high mobility has good characteristics.
[0120] <Method of manufacturing semiconductor device> Various methods can be used to manufacture the semiconductor element according to the embodiment of the present invention, and the manufacturing method is not particularly limited. For example, the manufacturing method of the semiconductor element described in International Publication No. 2018 / 180146 can be mentioned.
[0121] The method for forming the semiconductor layer is as described above, and it is preferable to use a coating method.
[0122] (Applicability of semiconductor devices) The semiconductor device according to the embodiment of the present invention is applicable to ICs of various electronic devices, wireless communication devices such as RFID tags, wireless power supply devices, thin film transistor arrays, sensors, and tamper detection systems.
[0123] <Circuit> The semiconductor element according to the embodiment of the present invention can be applied to various circuits. For example, analog circuits such as rectifier circuits, logic circuits such as NOT circuits, NAND circuits, NOR circuits, AND circuits, and OR circuits, combinational circuits and sequential circuits using them, and integrated circuits such as memories, microprocessors, and logic ICs can be used. Such circuits can be used in various electronic devices. Since the semiconductor element according to the embodiment of the present invention has high n-type semiconductor characteristics, it can be preferably used in the above-mentioned circuits, and in particular, it can be preferably used in complementary circuits composed of both p-type and n-type semiconductor elements. In addition, since the semiconductor layer contains a CNT complex, it is resistant to bending and stretching, and can be preferably used in flexible and bendable electronic devices.
[0124] <Wireless communication device> A wireless communication device according to an embodiment of the present invention, which has a semiconductor element according to an embodiment of the present invention, will be described. The wireless communication device is a device that communicates information using radio waves, such as a product tag, an anti-shoplifting tag, various tickets, or a smart card.
[0125] An example of the configuration of the wireless communication device is the wireless communication device described in International Publication No. 2018 / 180146. Various circuits are included, and the circuit of the present invention can be suitably used in those circuits or in part thereof.
[0126] <Product tag> The use of the wireless communication device is not particularly limited, but it can be applied to, for example, a product tag. A known product tag can be used, for example, one having a base and the wireless communication device covered by the base. If applied to a product tag equipped with an identification information return function, it becomes possible to simultaneously identify a large number of products at the checkout register without contact. Therefore, it is possible to facilitate and speed up the payment process compared to identification using a barcode.
[0127] Also, for example, when paying for a product, the reader / writer can transmit the product information read from the product tag to a POS (Point of Sale System) terminal. This function allows the POS terminal to register the sale of a product identified by the product information, making inventory management easier and faster.
[0128] <Thin-film transistor array> A thin film transistor (hereinafter, TFT) array can be obtained using the semiconductor element according to the embodiment of the present invention. For example, JP 2022-108261 A can be given as a configuration of the TFT array.
[0129] The TFT array according to the embodiment of the present invention can be used, for example, in active matrix driven liquid crystal displays, electronic paper, and the like.
[0130] <Sensor> The semiconductor device according to the embodiment of the present invention may be used in various sensors, for example, sensors for detecting temperature, moisture, gas, light, electromagnetic waves, radiation, pressure, and the like. EXAMPLES
[0131] The present invention will be described in more detail below based on examples. Note that the present invention is not limited to the following examples. The evaluation methods in the examples are described in the following (1).
[0132] (1) Evaluation of n-type semiconductor properties The source-drain current (Id)-source-drain voltage (Vsd) characteristics of the fabricated n-type semiconductor devices were measured when the gate voltage (Vg) was changed. The measurements were performed in air using a Semiconductor Characterization System Model 4200-SCS (Keithley Instruments Inc.). The mobility in the linear region was calculated from the change in the Id value at Vsd=+5V when Vg was changed from +10 to -5V. This was judged as follows, with A, B, and C being considered to have high mobility and high n-type semiconductor device characteristics. A+:5.0cm 2 / Vs or more A:4.0cm 2 / Vs smaller than 3.0cm 2 / Vs or more B:3.0cm 2 / Vs smaller than 2.0cm 2 / Vs or more C:2.0cm 2 / Vs smaller than 1.0cm 2 / Vs or more D:1.0cm 2 / Vs is smaller.
[0133] (Example of composition preparation) (1) Preparation example 1 of gate insulating layer material; Insulating material solution A A three-neck flask was charged with 18.75 g (0.08 mol) of 3-acryloxypropyltrimethoxysilane, 5.25 g (0.02 mol) of 3-trimethoxysilylpropylsuccinic anhydride, 24.84 g (0.10 mol) of 1-naphthyltrimethoxysilane, 171.78 g (100 parts by mass of particle content per 100 parts by mass of the mass (35.39 g) when the organosilane is completely condensed) of "Optraike (registered trademark)" TR-550 (manufactured by JGC Catalysts and Chemicals Co., Ltd.), which is a 20.6 mass% titanium oxide-silicon oxide composite particle methanol dispersion, and 131.44 g of diacetone alcohol. An aqueous phosphoric acid solution prepared by dissolving 0.244 g of phosphoric acid (0.50 mass% relative to the charged monomer) in 11.16 g of water was added over 10 minutes while stirring at room temperature. After that, the flask was immersed in a 40°C oil bath and stirred for 60 minutes, and the oil bath was heated to 115°C over 30 minutes. One hour after the start of the temperature increase, the internal temperature of the solution reached 100°C, and it was heated and stirred for 2 hours from that point (internal temperature was 100 to 110°C). After cooling the resin solution obtained by heating and stirring in an ice bath, anion exchange resin and cation exchange resin were added at 2% by weight each relative to the resin solution, and the mixture was stirred for 12 hours. After stirring, the anion exchange resin and cation exchange resin were removed by filtration to obtain a solution of polysiloxane bound to inorganic particles. Then, 2.29 g of DPHA ("KAYARAD (registered trademark)", manufactured by Nippon Kayaku Co., Ltd.; dipentaerythritol hexaacrylate) and 0.34 g of OXE-01 ("Irgacure (registered trademark)", manufactured by BASF Co., Ltd.) were used to obtain an insulating material solution A.
[0134] (2) Preparation Example 1 of Second Insulating Layer Material: Second Insulating Layer Solution A 2.5 g of polymethyl methacrylate (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) was dissolved in 7.5 g of N,N-dimethylformamide to prepare polymer solution A. Next, 1 g of tetrathiafulvalene (manufactured by Tokyo Chemical Industry Co., Ltd.) was dissolved in 9.0 g of N,N-dimethylformamide to prepare compound solution A. 0.30 g of compound solution A was added to 0.68 g of polymer solution A to obtain second insulating layer solution A.
[0135] (3) Preparation Example 1 of Semiconductor Layer Material: Semiconductor Layer Solution A The semiconducting CNTs and metallic CNTs were separated as follows.
[0136] CNT-A (Meijo Nano Carbon Co., Ltd., MEIJO eDIPS EC1.5) and sodium cholate (SC) were mixed in water (purified water purified by distillation) measured so that the SC concentration was 0.5 mass% and the CNT concentration was 0.1 mass%. 100 g of the mixture was irradiated with ultrasonic waves (50% output, 3 hours) using an ultrasonic homogenizer (Branson: Digital Sonifier Models 250). The obtained CNT dispersion was set in an ultracentrifuge (HITACHI, himac CS100GXII) and processed at 50,000G for 30 minutes to settle and remove impurities that were mixed in during CNT synthesis. This was used as the raw CNT dispersion.
[0137] Sodium dodecylsulfonate (SDS) was added to the obtained raw CNT dispersion liquid so that the SDS concentration was 0.5% by mass, and raw CNT dispersion liquid 2 with SC concentration and SDS concentration of 0.5% by mass was obtained. This raw CNT dispersion liquid 2 was charged into a column filled with gel, and an aqueous solution with SC concentration and SDS concentration of 0.5% by mass was used as a developing liquid to develop the raw CNT dispersion liquid. After the metallic CNTs flowed out, the developing liquid was switched to an aqueous solution with SC concentration of 0.5% by mass to obtain a CNT dispersion liquid with a high semiconducting CNT ratio. SDS was charged into the obtained CNT dispersion liquid, and the CNT dispersion liquid was adjusted to a CNT dispersion with SC concentration and SDS concentration of 0.5% by mass, and was again charged into a column filled with gel. Again, an aqueous solution with SC concentration and SDS concentration of 0.5% by mass was used as a developing liquid to develop the raw CNT dispersion liquid. After the metallic CNTs flowed out, the developing liquid was switched to an aqueous solution with SC concentration of 0.5% by mass to obtain a CNT dispersion liquid 3 with an even higher semiconducting CNT ratio. The absorption spectrum of the obtained CNT dispersion 3 was measured in the wavelength range of 300 nm to 1100 nm using a spectrophotometer (JASCO V-770), and the content of semiconducting CNTs in the CNTs was evaluated, and the content was found to be 96.4% by weight.
[0138] The obtained CNT dispersion 3 was pressure filtered using a membrane filter paper with an aperture of 0.1 μm manufactured by Millipore Corp. The filtered CNT composition was washed twice with about 50 mL of methanol, twice with about 50 mL of water, twice with about 50 mL of methanol, and finally with about 50 mL of chloroform to obtain semiconducting CNT-A in the form of a chloroform wet cake.
[0139] (4) Preparation Example 1 of Semiconductor Layer Material; CNT Dispersion A A conjugated polymer having the repeating structural unit [5] was synthesized as follows.
[0140] 0.20g of 1,4-dibromo-2,5-dihexylbenzene and 0.33g of 9,9-di-octylfluorene-2,7-diboronic acid bis(pinacol) were dissolved in 30mL of toluene. 10mL of water, 0.65g of potassium carbonate, 20mg of [1,1'-bis(diphenylphosphino)ferrocene]palladium(II) dichloride dichloromethane adduct and 1 drop of Aliquat(R)336 were added thereto, and the mixture was stirred at 100°C for 5 hours under a nitrogen atmosphere. 0.10g of bromobenzene was then added, and the mixture was stirred at 100°C for 1 hour. 50mL of methanol was added to the obtained solution, and the resulting solid was filtered and washed with methanol, water, and methanol in that order. The obtained solid was dissolved in chloroform, filtered through Celite and then passed through a silica gel short column (eluent: chloroform), and then concentrated to dryness to obtain 0.21 g of conjugated polymer 5 having the repeating structural unit [5].
[0141] 1.0 mg of semiconducting CNT-A was added to a 10 mL solution of 5.0 mg of conjugated polymer 5 in chloroform, and the mixture was stirred ultrasonically for 2 hours at 40% output using an ultrasonic homogenizer (VCX-500 manufactured by Tokyo Rikakikai Co., Ltd.) while cooling on ice, to obtain CNT dispersion liquid 1. Next, the CNT dispersion liquid 1 was filtered using a membrane filter (pore size 10 μm, diameter 25 mm, Omnipore membrane manufactured by Millipore Corporation). After adding 8 mL of 1,2-dichlorobenzene to the obtained filtrate, the low boiling point solvent chloroform was distilled off using a rotary evaporator to obtain CNT dispersion liquid 2. 1,2-dichlorobenzene was added to CNT dispersion liquid 2 to adjust the concentration, and CNT dispersion liquid A (CNT composite concentration relative to the solvent: 0.08 g / L) was obtained.
[0142] (5) Semiconductor Layer Material Preparation Example 2: CNT Dispersion B 0.17 g of conjugated polymer 27 having the repeating structural unit
[27] was obtained in the same manner as in the synthesis of conjugated polymer 5, except that 0.13 g of 1,4-dibromo-2,5-dimethylbenzene was used instead of 0.20 g of 1,4-dibromo-2,5-dihexylbenzene.
[0143] A CNT dispersion B was obtained in the same manner as in the preparation example of the CNT dispersion A, except that the conjugated polymer 27 was used instead of the conjugated polymer 5.
[0144] (6) Preparation Example 3 of Semiconductor Layer Material; CNT Dispersion C 0.19 g of conjugated polymer 31 having the repeating structural unit
[31] was obtained in the same manner as in the synthesis of conjugated polymer 5, except that 0.16 g of 4,7-dibromo-5,6-dimethyl-2,1,3-benzothiadiazole was used instead of 0.20 g of 1,4-dibromo-2,5-dihexylbenzene.
[0145] A CNT dispersion C was obtained in the same manner as in the preparation example of the CNT dispersion A, except that the conjugated polymer 31 was used instead of the conjugated polymer 5.
[0146] (7) Preparation Example 4 of Semiconductor Layer Material; CNT Dispersion D 0.19 g of conjugated polymer 32 having the repeating structural unit
[32] was obtained in the same manner as in the synthesis of conjugated polymer 5, except that 0.16 g of 4,7-dibromo-5,6-difluoro-2,1,3-benzothiadiazole was used instead of 0.20 g of 1,4-dibromo-2,5-dihexylbenzene.
[0147] A CNT dispersion D was obtained in the same manner as in the preparation example of the CNT dispersion A, except that the conjugated polymer 32 was used instead of the conjugated polymer 5.
[0148] (8) Preparation Example 5 of Semiconductor Layer Material; CNT Dispersion E 0.16 g of poly[(9,9-dioctylfluorenyl-2,7-diyl)-(1,4-phenylene)] was obtained in the same manner as in the synthesis of Conjugated Polymer 5, except that 0.12 g of 1,4-dibromobenzene was used instead of 0.20 g of 1,4-dibromo-2,5-dihexylbenzene.
[0149] A CNT dispersion E was obtained in the same manner as in the preparation example of the CNT dispersion A, except that poly[(9,9-dioctylfluorenyl-2,7-diyl)-(1,4-phenylene)] was used instead of the conjugated polymer 5.
[0150] (9) Preparation Example 6 of Semiconductor Layer Material; CNT Dispersion F 0.22 g of conjugated polymer 8 having a repeating structural unit [8] was obtained in the same manner as in the synthesis of conjugated polymer 5, except that 0.21 g of 1,4-dibromo-2,5-bis(hexyloxy)benzene was used instead of 0.20 g of 1,4-dibromo-2,5-dihexylbenzene.
[0151] A CNT dispersion F was obtained in the same manner as in the preparation example of the CNT dispersion A, except that the conjugated polymer 8 was used instead of the conjugated polymer 5.
[0152] (10) Semiconductor Layer Material Preparation Example 7: CNT Dispersion G 0.32 g of conjugated polymer 37 having a repeating structural unit
[37] was obtained in the same manner as in the synthesis of conjugated polymer 32, except that 0.53 g of 2,2'-(9,9,9',9'-tetraoctyl-[2,2'-bifluorene]-7,7'-diyl)bis(4,4,5,5-tetramethyl)-1,3,2-dioxaborolane) was used instead of 0.33 g of 9,9-dioctylfluorene-2,7-diboronic acid bis(pinacol).
[0153] A CNT dispersion G was obtained in the same manner as in the preparation example of the CNT dispersion A, except that the conjugated polymer 37 was used instead of the conjugated polymer 5.
[0154] (11) Semiconductor Layer Material Preparation Example 8: CNT Dispersion H 0.24 g of conjugated polymer 40 having the repeating structural unit
[40] was obtained in the same manner as in the synthesis of conjugated polymer 5, except that 0.24 g of 5,8-dibromo-6,7-difluoro-2,3-dihexylquinoxaline was used instead of 0.20 g of 1,4-dibromo-2,5-dihexylbenzene.
[0155] A CNT dispersion H was obtained in the same manner as in the preparation example of the CNT dispersion A, except that the conjugated polymer 40 was used instead of the conjugated polymer 5.
[0156] (12) Preparation Example 9 of Semiconductor Layer Material; CNT Dispersion I 0.24 g of conjugated polymer 45 having the repeating structural unit
[45] was obtained in the same manner as in the synthesis of conjugated polymer 32, except that 0.41 g of 2,2'-((9,9-dioctylfluorene-2,7-diyl)bis(4,1-phenylene)bis(4,4,5,5-tetramethyl)-1,3,2-dioxaborolane) was used instead of 0.33 g of 9,9-dioctylfluorene-2,7-diboronic acid bis(pinacol).
[0157] CNT dispersion I was obtained in the same manner as in the preparation example of CNT dispersion A, except that conjugated polymer 45 was used instead of conjugated polymer 5.
[0158] Example 1 First, a semiconductor device having the configuration shown in FIG. 1 was fabricated in the following manner.
[0159] Gold was vacuum-deposited to a thickness of 50 nm through a mask on a glass substrate 1 (film thickness 0.7 mm) by resistance heating to form a gate electrode 2. Next, insulating material solution A was spin-coated (800 rpm x 20 seconds) onto the glass substrate on which the gate electrode 2 was formed, and dried by heating at 110°C for 2 minutes to obtain a coating film. The formed coating film was set in an i-line stepper (DSW-8000 manufactured by GCA) and exposed to 400 mJ / cm 2The entire surface of the coating film was exposed to light at an exposure dose of 100 nm. After exposure, the film was developed with a 2.38 wt % TMAH aqueous solution for 60 seconds, and then rinsed with pure water. This film was heated at 180°C for 60 minutes using a hot plate to form a gate insulating layer 3 with a thickness of 400 nm. Next, gold was vacuum-deposited on the gate insulating layer 3 by a resistance heating method to a thickness of 50 nm, and a photoresist (product name "LC140-10cP", manufactured by Rohm and Haas Co., Ltd.) was spin-coated thereon (1000 rpm x 20 seconds), and dried by heating at 100°C for 10 minutes. The photoresist film thus prepared was exposed to light through a mask using a parallel light mask aligner (PLA-501F manufactured by Canon Inc.), and then shower-developed with a 2.38 wt % TMAH aqueous solution for 60 seconds using an automatic developing device (AD-2000 manufactured by Takizawa Sangyo Co., Ltd.), and then washed with water for 30 seconds. Thereafter, the substrate was etched with AURUM-302 (trade name, manufactured by Kanto Chemical Co., Ltd.) for 5 minutes, and then washed with water for 30 seconds. The substrate was immersed in AZ Remover 100 (trade name, manufactured by Merck Performance Materials Co., Ltd.) for 5 minutes to remove the resist, washed with water for 30 seconds, and then heated and dried at 120°C for 20 minutes to form a source electrode 5 and a drain electrode 6. The width (channel width) of both electrodes was 100 μm, and the distance (channel length) between both electrodes was 10 μm. 400 pL of CNT dispersion A was dropped onto the substrate on which the electrodes were formed using an inkjet device (manufactured by Cluster Technology Co., Ltd.), and heat-treated on a hot plate under a nitrogen stream at 150°C for 30 minutes to form a semiconductor layer 4. As a result, a semiconductor element having the configuration shown in FIG. 1 was obtained. Next, 5 μL of the second insulating layer solution A was dropped onto the semiconductor layer 4 so as to cover the semiconductor layer 4, and heat-treated at 110° C. for 30 minutes under a nitrogen flow to form a second insulating layer 8. In this way, an n-type semiconductor element was obtained. The obtained n-type semiconductor element was evaluated according to the above-mentioned evaluation method (1).
[0160] Examples 2 to 8, Comparative Example 1 An n-type semiconductor element was produced and evaluated in the same manner as in Example 1, except that CNT dispersions B to I, as shown in Table 1, were used instead of CNT dispersion A.
[0161] [Table 1] [Explanation of symbols]
[0162] 1 Base material 2. Gate electrode 3 Gate insulation layer 4 Semiconductor layer 5. Source Electrode 6 Drain electrode 7. CNT Composite 8 Second insulating layer
Claims
1. A carbon nanotube composite having a conjugated polymer attached to at least a portion of the surface of a carbon nanotube, the conjugated polymer having a repeating structural unit represented by the following general formula (1) or (2): 【Chemistry 1】 【Chemistry 2】 (In the general formula (1), X represents a structure represented by the general formula (3). 1 represents a 6- or higher membered arylene group or a 6- or higher membered heteroarylene group, and represents a structure different from X. In general formula (2), X represents a structure represented by general formula (3). A 2 represents an arylene group having 6 or more members or a heteroarylene group having 6 or more members. B represents an ethenylene group, an ethynylene group, an arylene group, or a heteroarylene group. m represents an integer of 1 to 20. When two or more Bs are present, each B may be the same or different. A 2 and B may be the same or different from each other.) 【Chemistry 3】 (In general formula (3), R 1 represents an alkyl group, an alkenyl group, an alkynyl group, an aryl group, a heteroaryl group, an alkoxy group, an aryloxy group, a heteroaryloxy group, an alkylsulfanyl group, an arylsulfanyl group, a heteroarylsulfanyl group, a halogen atom, a cyano group, a formyl group, a carbamoyl group, an amino group, an alkylcarbonyl group, an arylcarbonyl group, a heteroarylcarbonyl group, a carboxy group, an alkoxycarbonyl group, an aryloxycarbonyl group, a heteroaryloxycarbonyl group, an alkylcarbonyloxy group, an arylcarbonyloxy group, a heteroarylcarbonyloxy group, or a silyl group. R 2 ~R 4 each independently represents a hydrogen atom, an alkyl group, an alkenyl group, an alkynyl group, an aryl group, a heteroaryl group, an alkoxy group, an aryloxy group, a heteroaryloxy group, an alkylsulfanyl group, an arylsulfanyl group, a heteroarylsulfanyl group, a halogen atom, a cyano group, a formyl group, a carbamoyl group, a mercapto group, an amino group, a nitro group, a nitroso group, a thionitroso group, an imino group, a sulfilimino group, an azo group, a diazo group, an alkylcarbonyl group, an arylcarbonyl group, a heteroarylcarbonyl group, a carboxy group, an alkoxycarbonyl group, an aryloxycarbonyl group, a heteroaryloxycarbonyl group, an alkylcarbonyloxy group, an arylcarbonyloxy group, a heteroarylcarbonyloxy group, or a silyl group. R 1 ~R 4 may be the same or different from each other. 3 and R 4 A ring structure may be formed by
2. The R 1 The carbon nanotube composite according to claim 1 , wherein is an alkyl group, an alkenyl group, an alkynyl group, an alkoxy group, an alkylsulfanyl group, a halogen atom, a cyano group, a formyl group, a carbamoyl group, an amino group, an alkylcarbonyl group, a carboxy group, an alkoxycarbonyl group, an alkylcarbonyloxy group, or a silyl group.
3. The R 1 is an alkyl group having 3 or less carbon atoms, an alkenyl group having 3 or less carbon atoms, an alkynyl group having 3 or less carbon atoms, an alkoxy group having 2 or less carbon atoms, an alkylsulfanyl group having 2 or less carbon atoms, or a halogen atom.
4. The R 3 is an alkyl group, an alkenyl group, an alkynyl group, an aryl group, a heteroaryl group, an alkoxy group, an aryloxy group, a heteroaryloxy group, an alkylsulfanyl group, an arylsulfanyl group, a heteroarylsulfanyl group, a halogen atom, a cyano group, a formyl group, a carbamoyl group, a mercapto group, an amino group, a nitro group, a nitroso group, a thionitroso group, an imino group, a sulfilimino group, an azo group, a diazo group, an alkylcarbonyl group, an arylcarbonyl group, a heteroarylcarbonyl group, a carboxy group, an alkoxycarbonyl group, an aryloxycarbonyl group, a heteroaryloxycarbonyl group, an alkylcarbonyloxy group, an arylcarbonyloxy group, a heteroarylcarbonyloxy group, or a silyl group.
5. The R 3 and R 4 The carbon nanotube composite according to claim 1 , wherein the ring structure is formed by
6. The carbon nanotube composite according to claim 5 , wherein the ring structure is an aromatic ring or a heteroaromatic ring.
7. A semiconductor element comprising a substrate, a source electrode, a drain electrode and a gate electrode, a semiconductor layer in contact with the source electrode and the drain electrode, and a gate insulating layer that insulates the semiconductor layer from the gate electrode, wherein the semiconductor layer contains the carbon nanotube composite according to claim 1.
8. The semiconductor device according to claim 7 , further comprising a second insulating layer in contact with the semiconductor layer on a side opposite to the gate insulating layer with respect to the semiconductor layer.
9. The semiconductor device of claim 8 , wherein the second insulating layer contains an electron donating compound.
10. 10. The method for manufacturing a semiconductor element according to claim 7, further comprising the step of forming the semiconductor layer by a coating method.
11. A circuit comprising the semiconductor element according to any one of claims 7 to 9.
12. A wireless communication device comprising at least the circuit according to claim 11 and an antenna.
13. A thin film transistor array comprising the semiconductor element according to any one of claims 7 to 9.
14. A sensor comprising the semiconductor element according to any one of claims 7 to 9.
Citation Information
Patent Citations
n-TYPE SEMICONDUCTOR ELEMENT, COMPLEMENTARY TYPE SEMICONDUCTOR DEVICE AND METHOD FOR MANUFACTURING SAME, AND WIRELESS COMMUNICATION DEVICE IN WHICH SAME IS USED
WO2017130836A1
N-type semiconductor element, method for producing n-type semiconductor element, wireless communication device and product tag
WO2019097978A1